2012
DOI: 10.1177/0899764012467084
|View full text |Cite
|
Sign up to set email alerts
|

National Campaigns for Charitable Causes

Abstract: The authors present the first cross-national comparison of more than 300 national campaigns for charitable causes in the Netherlands, Spain, Sweden, and the United States for the period 1950 to 2011. The authors study frequency and amounts raised, discuss successful and failed campaigns, and review the literature with regard to potential determinants of success. The authors group these determinants into three categories: (a) perceived characteristics of recipients, notably their need, agency, and blamelessness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 48 publications
(55 reference statements)
2
48
0
2
Order By: Relevance
“…Among the external motivators, the environmental variables and/or policies have been explored by Wiepking and Breeze () and Van Leeuwen and Wiepking (). These authors found that when the economy is in a recession, organisations that aim to raise funds need to pay more attention because donors tend to be more concerned about their own financial situation.…”
Section: External Motivators Of Donationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the external motivators, the environmental variables and/or policies have been explored by Wiepking and Breeze () and Van Leeuwen and Wiepking (). These authors found that when the economy is in a recession, organisations that aim to raise funds need to pay more attention because donors tend to be more concerned about their own financial situation.…”
Section: External Motivators Of Donationmentioning
confidence: 99%
“…Specifically, Guy and Patton (), Duncan (), Bekkers and Wiepking (), Germain et al (), Wiepking and Maas (), Grace and Griffin (), Verhaert and Van Den Poel (), , Wiepking and Bekkers (), Michel and Rieunier (), O'Reilly, Ayer, Pegoraro, Leonard, and Rundle‐Thiele (), Van Leeuwen and Wiepking (), Mews and Boenigk () have all sought to understand what factors motivate the donation of money, blood, goods, time, and organs. This literature identifies external motivations that may explain an individual donor's behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Miller says: "If people witness undeserved suffering, they will be motivated to re-establish 'justice'" (Miller, 1977, p. 144). On the other hand, it is often thought that victims of man-made disasters (including wars) are to blame in some way for their misfortune (Meijer, Bekkers, & Schuyt, 2005; see also van Leeuwen, 2000van Leeuwen, , 2012. Examples of those generally deemed to be in need through no fault of their own are victims of a natural disaster or famine, and children.…”
Section: The Innocent Victimmentioning
confidence: 99%
“…Next, we formulate and test generic hypotheses to explain the success of national campaigns (see also van Leeuwen and Wiepking, 2012, the introduction to this symposium). In this study, we investigate the success of national campaigns for charitable causes in the Netherlands between 1951 and 2011.…”
mentioning
confidence: 99%